Characteristics of Medically Transported Critically Ill Children with Respiratory Failure in Latin America: Implications for Outcomes - Serra, Jesus A.; Díaz, Franco; Cruces, Pablo; Carvajal, Cristobal; Nuñez, Maria J.; Donoso, A.; Bravo-Serrano, J.A.; Carbonell, M.; Courtie, C.; Fernández, A.; Martínez-Arroyo, L.; Martínez, J.; Menta, S.; Pedrozo-Ortiz, Luis; Wegner, A.; Monteverde-Fernández, Nicolas; Jaramillo-Bustamante, Juan C.; Jabornisky, Roberto; González-Dambrauskas, Sebastián; Kudchadkar, Sapna R.; Vásquez-Hoyos, Pablo; On behalf of LARed Network (Journal of Pediatric Intensive Care, 2021)
Several challenges exist for referral and transport of critically ill children in resource-limited regions such as Latin America; however, little is known about factors associated with clinical outcomes. Thus, we aimed to describe the characteristics of critically ill children in Latin America transferred to pediatric intensive care units for acute respiratory failure to identify risk factors for mortality. We analyzed data from 2,692 patients admitted to 28 centers in the Pediatric Collaborative Network of Latin America Acute Respiratory Failure Registry. Among patients referred from another facility (773, 28%), nonurban transports were independently associated with mortality (adjusted odds ratio = 9.4; 95% confidence interval: 2.4–36.3).
Keywords: patient transfer; critical illness; mortality; Latin America; hospitals; urban